Change of factual circumstances in the context of the issuance of judicial acts in civil cases - K. S. Ryzhkov (Правоприменение)
The subject of the study within the framework of this article are the norms of civil procedural law and arbitration procedural law concerning the issuance of judicial acts in connection with a change in factual circumstances relevant to the case. The purpose of the study is to identify and classify cases in which the current legislation and law enforcement practice allow the issuance of a new judicial act in connection with a change in the actual circumstances of the case. At the same time, the purpose of the study is related to the confirmation of the hypothesis about the diversity of the bases of such a classification.Within the framework of this study, the functional method, the system-structural method, the formal-legal method and the hermeneutic method were used. The use of these methods is due to the need to analyze a large volume of legal norms and judicial practice on the subject of the study. The article analyzes the legal mechanisms, the application of which is associated with the issuance of judicial acts in the framework of civil and arbitration proceedings based on changes in the factual circumstances of the case. The following mechanisms are identified as these mechanisms: the possibility of filing a claim with a new basis, revision of judicial acts under new circumstances, changing the method and procedure for the execution of a court decision, postponement and installment of the execution of a court decision, indexation of the amounts awarded.Cases of application of these mechanisms are classified according to the procedural order of consideration by the court of changes in circumstances and its consolidation in judicial acts, while the following types are distinguished: cases related to the consolidation of circumstances by making a new court decision on a claim with a new basis; cases related to the consolidation of circumstances by making a court ruling in connection with the emergence of new circumstances; cases related to the consolidation of circumstances by issuing a court ruling in connection with a change in the method and procedure for the execution of a court decision, postponement and installment of the execution of a court decision, indexation of the amounts awarded. Cases of the use of these mechanisms are also classified by the type of judicial act fixing such changes, while the following types are distinguished: cases related to the consolidation of circumstances by issuing a court decision; cases related to the consolidation of circumstances by issuing a court ruling.The author concludes that the use of the term "new circumstances" is incorrect in relation to certain grounds for reviewing judicial acts, in connection with which it is proposed to amend the norms of procedural legislation. In relation to these cases, it is proposed to use not the term "new circumstances", but the term "change in the content of legal norms or their interpretation that is relevant to the case".Based on the above, the purpose of the study has been fully achieved.